2020
DOI: 10.7150/jca.35614
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of the prognostic value of FAS mRNA in malignancies

Abstract: Background: FAS is a classical death receptor involved in the FAS/FAS ligand (FASL) apoptosis pathway and plays a role in anti-tumor activity. Some studies have recently reported that FAS can serve as an oncogene that promotes tumor proliferation and maintains the stemness of tumor cells. Hence, its prognostic value in malignancies remains controversial. Methods: we assessed the prognostic value of FAS mRNA in several types of tumors by online platforms including Kaplan-Meier Plotter and SurvExpress. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…However, they found that relapse-free survival was prolonged in FAS-positive cases compared to FAS negative ones ( 4 ). In addition, Chen et al, evaluating the prognostic value of FAS mRNA in various malignancies using online platforms, reported that higher expression of FAS was related to a poorer OS in AML patients (Hazard ratio, 1.57; P = 0.04) ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, they found that relapse-free survival was prolonged in FAS-positive cases compared to FAS negative ones ( 4 ). In addition, Chen et al, evaluating the prognostic value of FAS mRNA in various malignancies using online platforms, reported that higher expression of FAS was related to a poorer OS in AML patients (Hazard ratio, 1.57; P = 0.04) ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…FAS and GADD45A have been reported to play a role in inducing apoptosis and have also been previously identified to have a positive correlation with patient prognosis in patients with NSCLC. [59][60][61][62][63] DPYSL4 has been reported to function as a tumor suppressor, 64 and interestingly, DPYSL4 has also been reported to play a role in inducing necrosis. 65 However, necrosis was not an area of focus for this study, and 5-FU-miR-129's role in necrosis can be examined in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…RBM10 can regulate the selective cleavage of Fas transcripts ( 28 ). Fas is a classical death receptor involved in the Fas/Fas ligand (FasL) apoptosis pathway, which has anti-tumor activity ( 29 ), and can cause cascade reactions that lead to cell death. Fas is a pro-apoptotic protein that produces pro-apoptotic subtypes and anti-apoptotic subtypes through alternative splicing ( 30 ).…”
Section: Roles Of Rna-binding Motif Protein 10 In Regulating Tumor Dementioning
confidence: 99%